Targeting BCMA to Treat Multiple Myeloma: Updates From the 2021 ASH Annual Meeting - Guo, Ruiting; Lu, Wenyi; Zhang, Yi; Cao, Xinping; Jin, Xin; Zhao, Mingfeng (Frontiers in Immunology, 2022)
With the gradual improvement of treatment regimens, the survival time of multiple myeloma (MM) patients has been significantly prolonged. Even so, MM still is a nightmare with an inferior prognosis. B cell maturation antigen (BCMA) highly expresses on the surface of malignant myeloma cells. For the past few years, significant progress has made in various BCMA-targeted immunotherapies for treating patients with RRMM, including anti-BCMA mAbs, antibody-drug conjugates, bispecific T cell engagers, and BCMA-targeted chimeric antigen receptor-T cell therapy. The 63rd annual meeting of American Society of Hematology updated some information about the application of BCMA in MM. This review summarizes part of the related points presented at this conference.